Sistem Pendukung Keputusan Perhitungan Analisis Kesehatan Bank Dengan Metode Analytical Hierarchy Process (AHP) dan Metode CAMEL - Heni Ermewaningsih (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2022)
The bank’s health level is the ability of a bank to conduct banking operations normally and is able to meet all obligations well in ways that comply with banking regulations that apply. It is generally used to measure the health of a bank which is reflected in CAMEL, can be measured as the decision letter of the Board of Directors of Bank Indonesia Number 6/10/PBI date 12 April 2004 and Circulars BI Number 7/23/DPNP on 31 May 2004, about How the assessment of the level of health of public Bank. To help the process calculation analysis of the health of the bank will be made a decision support system of bank health analysis calculations. With the method of Analytical Hierarchy Process (AHP). Based on the result of research that has been carried out that the results of testing by the method of AHP to merangking aspects assessment on variabel CAMEL show that this method can be used for these aspects merangking properly. From the results of the calculation of the AHP proves that the level of health at the BRI Branch PT Sekadau gets an average of 3.897699 so that the results of PT BRI Branch Sekadau declared healthy.